2009
DOI: 10.1016/j.cub.2009.06.059
|View full text |Cite
|
Sign up to set email alerts
|

Attention Narrows Position Tuning of Population Responses in V1

Abstract: When attention is directed to a region of space, visual resolution at that location flexibly adapts, becoming sharper to resolve fine-scale details or coarser to reflect large-scale texture and surface properties. By what mechanism does attention improve spatial resolution? An improved signal-to-noise ratio (SNR) at the attended location contributes, because of retinotopically specific signal gain. Additionally, attention could sharpen position tuning at the neural population level, so that adjacent objects ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 27 publications
7
57
3
Order By: Relevance
“…Moreover, previous results showed that attention allocation not only caused signal enhancement in the calcarine cortex (Desimone and Duncan, 1995;, but also tuned receptive fields of neurons in V1, eventually leading to a sharpening of the spatial coding of attended visual stimuli (Fischer and Whitney, 2009). In light of these findings, our new ERP results for the C1 suggest that the primary feature or process that may be affected concurrently by load and affect is the actual perceptual encoding of the spatial position of the distractor stimulus shown in the upper visual field.…”
Section: Negative Affect Influences the Spatial Encoding Of The Distrmentioning
confidence: 91%
“…Moreover, previous results showed that attention allocation not only caused signal enhancement in the calcarine cortex (Desimone and Duncan, 1995;, but also tuned receptive fields of neurons in V1, eventually leading to a sharpening of the spatial coding of attended visual stimuli (Fischer and Whitney, 2009). In light of these findings, our new ERP results for the C1 suggest that the primary feature or process that may be affected concurrently by load and affect is the actual perceptual encoding of the spatial position of the distractor stimulus shown in the upper visual field.…”
Section: Negative Affect Influences the Spatial Encoding Of The Distrmentioning
confidence: 91%
“…In this framework, under LL (hence when some attentional capacity is left over), the peripheral stimuli might elicit stronger activations in early visual cortex, including in V1 (Rauss et al, 2009;Rees et al, 1997;Rossi & Pourtois, 2012;Schwartz et al, 2005). In this area, attention had been previously shown to boost signal strength and sharpen position tuning (Fischer & Whitney, 2009), eventually enhancing spatial resolution (Carrasco & Yeshurun, 2009;Yeshurun & Carrasco, 1998). By comparison, under HL, given that the residual attentional capacity is reliably reduced (Lavie, 2005), early visual responses are also significantly decreased (see Rauss et al, 2009;Schwartz et al, 2005 for converging evidence of an early modulation of V1 using a similar task), and spatial resolution eventually decreased.…”
Section: Coarse Vs Fine Spatial Encoding Under Load and Namentioning
confidence: 99%
“…Directing attention to the fovea boosts the response to stimuli near the attended target, while suppressing that to irrelevant stimuli distant from the attended location. The effect of attention can even reshape and shift the receptive fields (RFs) of single cells in monkey's MT [37] and in human V1 [38]. Is attention also instrumental in building spatiotopic selectivity?…”
Section: Spatiotopicitymentioning
confidence: 99%